Efficiency Evaluation Approach in Teaching Foreign Languages for Specific Purposes - Olga Aleksandrovna Drabinyastaya (Сибирское юридическое обозрение, 2011)
The article examines professional development of a future lawyer in a university environment. The author pays special attention to teaching foreign languages and describes the role of studying foreign languages by students on their way to professional career.